2003
DOI: 10.1074/jbc.m306752200
|View full text |Cite
|
Sign up to set email alerts
|

Glutamine Stimulates Argininosuccinate Synthetase Gene Expression through Cytosolic O-Glycosylation of Sp1 in Caco-2 Cells

Abstract: Glutamine stimulates the expression of the argininosuccinate synthetase (ASS) gene at both the level of enzyme activity and mRNA in Caco-2 cells. Searching to identify the pathway involved, we observed that (i) the stimulating effect of glutamine was totally mimicked by glucosamine addition, and (ii) its effect but not that of glucosamine was totally blocked by 6-diazo-5-oxo-L-norleucine (DON), an inhibitor of amidotransferases, suggesting that the metabolism of glutamine to glucosamine 6-phosphate was require… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
47
0
3

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(56 citation statements)
references
References 45 publications
6
47
0
3
Order By: Relevance
“…NF-jB, and another transcription factor, Sp1, have both been shown to mediate up-regulation of AS in response to IL-1b and glutamine, respectively, indicating that further validation of these pathways is warranted in ovarian (and other) tumours overexpressing TNF-a and AS. 22,23 The high levels of tumoral AS mRNA and protein expression, co-localising with TNF-a, suggest that inflammatory cytokines are involved in the regulation of this enzyme in vivo. Recent work identified both IL-1b and TNF-a as distinct regulators of AS in the Caco-2 epithelial cell line 22 ; previously, studies employed combinations of inflammatory cytokines to show that AS is inducible maximally (2-to 3-fold) by 24 hr in malignant cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…NF-jB, and another transcription factor, Sp1, have both been shown to mediate up-regulation of AS in response to IL-1b and glutamine, respectively, indicating that further validation of these pathways is warranted in ovarian (and other) tumours overexpressing TNF-a and AS. 22,23 The high levels of tumoral AS mRNA and protein expression, co-localising with TNF-a, suggest that inflammatory cytokines are involved in the regulation of this enzyme in vivo. Recent work identified both IL-1b and TNF-a as distinct regulators of AS in the Caco-2 epithelial cell line 22 ; previously, studies employed combinations of inflammatory cytokines to show that AS is inducible maximally (2-to 3-fold) by 24 hr in malignant cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been showed that glutamine stimulates ASS expression in rat hepatocytes and Caco-2 cells through O-glycosylation of Sp1. sites [71]. The expression of ASS also has been showed to be regulated by arginine [72].…”
Section: Why Ass Is Not Expressed In Certain Tumor Types ?mentioning
confidence: 99%
“…GLN is a key substrate required for optimal activity of the HBP (2,28). Furthermore, recent evidence reveals that GLN stimulates expression of the argininosuccinate synthetase (ASS) gene via O-glycosylation of Sp1 (2).…”
mentioning
confidence: 99%
“…Furthermore, recent evidence reveals that GLN stimulates expression of the argininosuccinate synthetase (ASS) gene via O-glycosylation of Sp1 (2). Thus, precedent exists for GLN utilizing the HBP to modify gene expression via Sp1.…”
mentioning
confidence: 99%